THE ROLE OF PRODUCT INNOVATION AND SUSTAINABILITY IN BUILDING BRAND TRUST AMONG GENERATION Z - Khotimah, Khusnul; Silvia, Dewi; Wijayanto, Gatot (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
Generation Z, as a group of young consumers who grew up in the digital age, has unique preferences towards brands, placing product innovation and sustainability as key factors in building brand trust. However, many companies face challenges in understanding how these two elements contribute synergistically to the formation of brand trust. This study aims to explore the relationship between product innovation, sustainability and brand trust among Generation Z through a qualitative approach. Data was collected from 15 respondents aged 18-24 through a Likert scale-based questionnaire and interviews. The results showed that 80% of respondents gave a high score to the perception of product innovation, while 85% rated sustainability as an important element in choosing a brand. Brand trust, with an average score of 4.3, is influenced by a brand's ability to authentically integrate innovation and sustainability. Thematic analysis of the interviews revealed that Generation Z values transparency and brands' long-term commitment to these values.